ESSAI EMPIRIQUE SUR LES DÉTERMINANTS DE L’ACTE ENTREPRENEURIAL DANS LE SECTEUR TEXTILE MAROCAIN - Omar Taouab (European Scientific Journal, ESJ, 2014)
Entrepreneurship and business creationis a key factor to enhance the vitality and development of the Moroccan economy especially when undertaken in areas of high economic impact including the textile sector. To delineate the main determinants of entrepreneurial activityfactors, wemobilized the theoretical model of planned behavior (Ajzen and Fishbein, 1991) and Shapiro’s model(1993) who consider the desirability of the act of undertake as a dependent variable of demographic variables and personality traits. Our results have directed us to the proposal of some actions to betaken to increase the likelihood of undertaking in this area. Eachproposed action isaccompanied by an approximation of the expected positive effects on endogenous variable due to a variation of a factor.